1975
DOI: 10.1111/j.1365-2818.1975.tb04014.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of autoradiographs by X‐ray spectroscopy

Abstract: SUMMARY Measurements of mass of developed silver in autoradiograms have been made using X‐ray microanalysis. This procedure has been applied to a scanning electron microscopic study of protease‐induced cell stimulation in 3H‐thymidine‐labelled bladder tissues in vitro. Differences in silver concentrations over individual nuclei were demonstrated by X‐ray analysis and quantitative data was obtained showing an increased rate of 3H‐thymidine incorporation in protease‐treated cultures. The initial evidence indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Thus, it was demonstrated that X-ray microanalysis by TEM mode was useful in quantifying silver grains in EMRAG instead of visual grain counting. In the literature, Hodges and Muir [10] were the first to quantify silver content on EMRAG obtained from cultured cells labeled with 3 H-thymidine by scanning electron microscopy (SEM) equipped with EDX, but they did so by observing the cell surface without confirming the nuclei and cell organelles surrounded with cytoplasm. Our reports [27,30,32] were the first to quantify the silver grains by TEM mode observing both the silver grains and the nuclei and cell organelles.…”
Section: Silver Grains In Radioautographs (Ag)mentioning
confidence: 99%
“…Thus, it was demonstrated that X-ray microanalysis by TEM mode was useful in quantifying silver grains in EMRAG instead of visual grain counting. In the literature, Hodges and Muir [10] were the first to quantify silver content on EMRAG obtained from cultured cells labeled with 3 H-thymidine by scanning electron microscopy (SEM) equipped with EDX, but they did so by observing the cell surface without confirming the nuclei and cell organelles surrounded with cytoplasm. Our reports [27,30,32] were the first to quantify the silver grains by TEM mode observing both the silver grains and the nuclei and cell organelles.…”
Section: Silver Grains In Radioautographs (Ag)mentioning
confidence: 99%
“…10a and lob) as a consequence of the.high atomic number contrast of the heavy metal against the lower contrast of the biological material (Hodges & Muir, 1976;Bowen et al, 1983). Where necessary, further identification or quantification of silver grains should be possible by X-ray analysis as previously discussed (Hodges & Muir, 1975;Junger & Bachmann, 1980). By immunofluorescence, the He117 fibroblasts displayed the characteristic fibrillar network of extracellular fibronectin using either monospecific or monoclonal antifibronectin antibodies (Fig.…”
Section: Observations Of Emulsion-coated [3h]mentioning
confidence: 97%
“…9a, b and 10a, b). Where necessary, further identification or quantification of silver grains should be possible by X-ray analysis as previously discussed (Hodges & Muir, 1975;Junger & Bachmann, 1980). The appearance of the silver grains was not always easy to recognize when samples were examined in the secondary electron imaging (SEI) mode and could be confused with the microvillous configurations of the RT4 cell surface.…”
Section: Sem Analysis Of Autoradiogramsmentioning
confidence: 99%
“…A related field, the exploration of which is only beginning, is the use of cell surface markers incorporating distinctive elements (Baccetti & Burrini, 1977;Hoyer et al, 1979) which can be detected by X-ray microanalysis, rather than the more usual fluorescent or enzyme markers. X-ray microanalysis has also been proposed for the quantification of silver grains on autoradiographs (Hodges & Muir, 1975) but, again, this application has not yet been much employed.…”
Section: Diffusible Ionsmentioning
confidence: 99%